Association between colorectal polyps and hypertension treatment. Issue 11 (November 2015) - Watanabe, Yoshitaka; Yamaji, Yutaka; Kobayashi, Yuka; Yoshida, Shuntaro; Sugimoto, Takafumi; Yamada, Atsuo; Watabe, Hirotsugu; Hirata, Yoshihiro; Koike, Kazuhiko
Abstract : Objective: Patients who take drugs regularly are increasing, not least due to metabolic and orthopedic diseases. In the present study we aimed to investigate the association between the use of drugs, such as non‐steroidal anti‐inflammatory drugs (NSAIDs) and low‐dose aspirin, and colorectal polyps diagnosed based on colonoscopic findings. Methods: In total, 1318 consecutive patients who underwent total colonoscopy for the first time were cross‐sectionally analyzed. Personal data including comorbidities and all medications were obtained by a questionnaire. Their blood pressure, body weight and waist circumference were measured just before the colonoscopic examination. Results: Colorectal polyps were found in 577 (43.8%) patients, with a prevalence of 57.6% (296/514) in patients receiving antihypertensive treatment and 35.0% (281/804) in patients not undergoing such treatment. A multivariate analysis showed that age, waist circumference, alcohol consumption, smoking and the use of antihypertensive drugs were independent risk factors for colorectal polyps. In a secondary multivariate analysis incorporating the parameters of measured blood pressure and medication status, the number of antihypertensive drugs was strongly associated with the risk of colorectal polyps, whereas blood pressure showed no significant association. Conclusions: The use of antihypertensive drug may be a risk factor for colorectal polyps. Furthermore, this risk increases with the intensive use of antihypertensive drugs.